2022
DOI: 10.1371/journal.pone.0271288
|View full text |Cite|
|
Sign up to set email alerts
|

Detecting underreporters of abortions and miscarriages in the national study of family growth, 2011–2015

Abstract: This paper draws on individual-level data from the National Study of Family Growth (NSFG) to identify likely underreporters of abortion and miscarriage and examine their characteristics. The NSFG asks about abortion and miscarriage twice, once in the computer-assisted personal interviewing (CAPI) part of the questionnaire and the other in the audio computer-assisted self-interviewing (ACASI) part. We used two different methods to identify likely underreporters of abortion and miscarriage: direct comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…First, administrative health records on induced abortion are often inaccurate and incomplete. In addition, research has consistently shown that women responding to social surveys are likely to underreport experiences with abortion (11,12), and women presenting with post-abortion complications in facilities often report induced abortions as miscarriages (13). As a result of these di culties, there is very little available evidence on abortion in Liberia.…”
Section: Introductionmentioning
confidence: 99%
“…First, administrative health records on induced abortion are often inaccurate and incomplete. In addition, research has consistently shown that women responding to social surveys are likely to underreport experiences with abortion (11,12), and women presenting with post-abortion complications in facilities often report induced abortions as miscarriages (13). As a result of these di culties, there is very little available evidence on abortion in Liberia.…”
Section: Introductionmentioning
confidence: 99%